USER-DRIVEN INNOVATION: TOWARDS A NEW INNOVATION PARADIGM - Slavica Rocheska; Olivera Kostoska; Marjan Angeleski; Gjorgji Mancheski (Economic Review)
The holistic approach to innovation includes establishing a wide range of interactions among different actors which implies development and expansion of methods, approaches and tools for improving the innovation. This paper analyzes the impact of customers and users on promoting innovation of companies. In this context, the authors advocate different methods and approaches for establishing interactions between the customer and the company and for providing the customer involvement in the process of innovation. Therefore, the paper aims at presenting an analytical overview of the methods and tools by which users influence companies’ process of innovation. It will also propose a conceptual framework as regards the user involvement in different stages of the innovation process.